The Political Attitudes of Divided European Citizens: Public Opinion and Social Inequalities in Comparative and Relational Perspective - Lahusen, Christian (Routledge Studies in Political Sociology, 2020)
The Open Access version of this book, available at http://www.taylorfrancis.com/books/e/9781003046653, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license. This book unveils the significant impact of the European integration process on the political thinking of European citizens. With close attention to the interrelation between social and political divisions, it shows that an integrated Europe promotes consensus but also propagates growing dissent among its citizens, with both objective inequalities and the subjective perception of these inequalities fuelling political dissent. Based on original data sets developed from two EU-funded projects across eight and nine European countries, the volume demonstrates the important role played by the social structure of European social space in conditioning political attitudes and preferences. It shows, in particular, that Europeans are highly sensitive to unequal living conditions between European countries, thus affecting their political support of national politics and the European Union. As such, it will appeal to scholars of sociology and politics with interests in Europe and the European Union, European integration and political sociology.